Notes on the bee genus Alloscirtetica Holmberg, 1909 in northern Chile with the description of two new altiplanic species and a key for the Chilean species of Eucerini (Hymenoptera: Apidae) - Vivallo, Felipe (Zootaxa, 2009)
In this paper two new species of the bee genus Alloscirtetica collected in the altiplanic region of northern Chile are described. The species Alloscirtetica larocai Urban, from Rivadavia, Region of Coquimbo is proposed as new junior synonym of A. lanosa Urban. The Peruvian species A. weyrauchi is reported from northern Chile for the first time extendingits known distributional range southward. A compilation of the distributional and floral records of the Chilean species of Eucerini is given, including a key for the indentification of all the species of the tribe occurring in Chile.